2012
DOI: 10.1371/journal.pone.0044064
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CYP2C9 and VKORC1 on Patient Response to Warfarin: A Systematic Review and Meta-Analysis

Abstract: BackgroundWarfarin is a highly effective anticoagulant however its effectiveness relies on maintaining INR in therapeutic range. Finding the correct dose is difficult due to large inter-individual variability. Two genes, CYP2C9 and VKORC1, have been associated with this variability, leading to genotype-guided dosing tables in warfarin labeling. Nonetheless, it remains unclear how genotypic information should be used in practice. Navigating the literature to determine how genotype will influence warfarin respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
136
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 136 publications
(401 reference statements)
6
136
1
3
Order By: Relevance
“…1,[25][26][27] The PREDICT project, which was launched institutionally in 2010, provides patients with a pharmacogenomic profile of possible sensitivities to these specific medications. 25 There were over 14,000 genotyped patients within the PREDICT database, panels which included genotypes of both VKORC1 and CYP2C9.…”
Section: S147mentioning
confidence: 99%
See 2 more Smart Citations
“…1,[25][26][27] The PREDICT project, which was launched institutionally in 2010, provides patients with a pharmacogenomic profile of possible sensitivities to these specific medications. 25 There were over 14,000 genotyped patients within the PREDICT database, panels which included genotypes of both VKORC1 and CYP2C9.…”
Section: S147mentioning
confidence: 99%
“…One major factor is the individual's genetic makeup. 1 Debate has emerged as to whether genetic testing is indicated prior to initiation of warfarin therapy, as persistently subtherapeutic anticoagulation may lead to fatal thromboembolic events, while supratherapeutic anticoagulation can lead to bleeding. A recent prospective randomized trial of a clinical vs. genotype-guided warfarin-dosing algorithm has been reported in patients anticoagulated for atrial fibrillation or venous thromboembolic disease, revealing that genetic-based dosing leads to greater time spent in, and shorter time to reach therapeutic international normalized ratio (INR) range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, age, concomitant drugs, comorbidities, vitamin K intake and other environmental factors alongside genetic predispositions are responsible for almost half of warfarin dose variability [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a recent meta-analysis [4], Jorgensen et al showed that for the Caucasian ethnic group, the pooled effect estimate of the VKORC SNP rs 7294 on warfarin dosing was nonsignificant for heterozygotes versus wild-types, but was statistically significant for mutant-types versus wild-types.…”
mentioning
confidence: 99%